(untitled) (Pakistan Journal of Scientific Research, 2022)
From the start of time, electricity has been transmitted using the traditional method of AC transmission over large distances. But using this transmission technique, there are many issues and disadvantages, including transmission losses and having an extremely small power factor due to transmission line material. To remedy these losses, researchers plan to devise another transmission system named a high voltage direct current (HVDC). Using the HVDC system, bulk power can be transmitted over a large distance without losses and with greater efficiency. Using this method, the cost is also improved, and the security is overwhelmed. The purpose is to devise such a system and simulate the HVDC system under various parameters of system protection and fault conditions. To simulate the research, MATLAB/SIMULINK tool is exploited and verified, which shows better performance than AC transmission.